Supply-Side Competitiveness on The Polish Apple Market Against Other V4 Countries - Anna S. KOWALSKA; Anna OLSZAŃSKA; Joanna SZYMAŃSKA; Klaudia GURKOWA (Communications of International Proceedings, 2022)
The article aimed to assess the supply side of the Polish apple market and its competitiveness in relation to other V-4 countries and the group of countries belonging to the EU-28, EU-13 and EU-15. The subject of the research was the area and volume of apple production. The source material came from the FAOSTAT database. Data from 2004–2019 were used. The article assesses the concentration on the apple market and the degree of its monopolization. For this purpose, the Gini Index (K), Concentration Ratio (CR) and Herfindahl-Hirschman Index (HHI) were used. Poland is a significant producer of apples in the EU-28 and the most important one in the V-4 countries. Research has shown that the closest neighbours (including other V-4 countries) reduce the area of orchards and thus the production of apples. Little competition, good geographic location and growing returns to scale create opportunities for Polish fruit growers for further expansion on the European market.
Keywords: fruit; apples; production volume; competitiveness.